1993
DOI: 10.1083/jcb.122.4.775
|View full text |Cite
|
Sign up to set email alerts
|

A cytosolic complex of p62 and rab6 associates with TGN38/41 and is involved in budding of exocytic vesicles from the trans-Golgi network

Abstract: Abstract. TGN38/41, an integral membrane protein predominantly localized to the trans-Golgi network, has been shown to cycle to the plasma membrane and return to the TGN within 30 min. (Ladinsky, M. S., and K. E. Howell. 1992. Eur. J. Cell BioL 59:92-105). In characterizing the proteins which associate with TGN38/41, a peripheral 62-kD protein, two forms of rab6 and two other small GTP-binding proteins were identified by coimmunoprecipitation. However, •90% of the 62-kD protein is cytosolic and is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(79 citation statements)
references
References 50 publications
3
74
0
Order By: Relevance
“…TGN38 was originally identified as a resident of the TGN (Luzio et al, 1990) but more recent work has shown that it cycles between the TGN and the cell surface (Jones et al, 1993;Reaves et al, 1993). Movement to the cell surface occurs via exocytic vesicles (Jones et al, 1993) and is followed by retrieval which requires a signal present in the cytoplasmic domain that has been localized to the sequence SDYQRL (Bos et al, 1993;Humphrey et ai., 1993;Wong and Hong, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGN38 was originally identified as a resident of the TGN (Luzio et al, 1990) but more recent work has shown that it cycles between the TGN and the cell surface (Jones et al, 1993;Reaves et al, 1993). Movement to the cell surface occurs via exocytic vesicles (Jones et al, 1993) and is followed by retrieval which requires a signal present in the cytoplasmic domain that has been localized to the sequence SDYQRL (Bos et al, 1993;Humphrey et ai., 1993;Wong and Hong, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Movement to the cell surface occurs via exocytic vesicles (Jones et al, 1993) and is followed by retrieval which requires a signal present in the cytoplasmic domain that has been localized to the sequence SDYQRL (Bos et al, 1993;Humphrey et ai., 1993;Wong and Hong, 1993). Retrieved TGN38 first moves to the endosomes and then to the TGN (Bos et al, 1993;Humphrey et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…6) with A R F and with the trans-Golgi markers, TGN38 (25), rab6 (3,20), and caveolin (16). A R F (Fig.…”
Section: Ga Subunits Partially Cofractionate With Trans-golgi Markersmentioning
confidence: 99%
“…We initiated this project in studying the Golgi cleared of proteins in transit with the following long-range objectives: to characterize the basic structure of the Golgi ribbon and to obtain a Golgi fraction where in vivo structure remained relatively intact in order to identify endogenous Golgi proteins and activities. This latter objective led us to revise the Golgi fractionation procedure we had been using for our functional assays of vesicle budding from the trans-Golgi network (TGN; Salamero et al, 1990;Jones et al, 1993). The modified procedure provides highly enriched intact stacked Golgi fractions with and without proteins in transit.…”
Section: Introductionmentioning
confidence: 99%